2018
DOI: 10.1371/journal.pone.0202664
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of Escherichia coli and LPS by mammary epithelial cells is modulated by O-antigen chain and CD14

Abstract: Escherichia coli is one of the major pathogens causing mastitis in dairy cattle. Yet, the factors which mediate the ability for E. coli to develop in the bovine mammary gland remain poorly elucidated. In a mouse model, infections induced by the reference mastitis E. coli P4 showed a strong colonisation of the mammary gland, while this strain had a low stimulating power on cells of the PS bovine mammary epithelial cell line. In order to understand if such a reduced response contributes to the severity of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…This would be consistent with previous studies showing that smooth LPS (S-LPS) depends on CD14 to activate cells [42,45]. On the other hand, it is established that rough LPS (R-LPS) depends on CD14 mainly for TLR4 endocytosis [24,25], although some studies reported both in vitro and in vivo that R-LPS could benefit from the presence of CD14 [24,46]. Accordingly, several other studies have described R-LPS as a more potent agonist of the innate immune system than S-LPS [42,4649].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This would be consistent with previous studies showing that smooth LPS (S-LPS) depends on CD14 to activate cells [42,45]. On the other hand, it is established that rough LPS (R-LPS) depends on CD14 mainly for TLR4 endocytosis [24,25], although some studies reported both in vitro and in vivo that R-LPS could benefit from the presence of CD14 [24,46]. Accordingly, several other studies have described R-LPS as a more potent agonist of the innate immune system than S-LPS [42,4649].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, it is established that rough LPS (R-LPS) depends on CD14 mainly for TLR4 endocytosis [24,25], although some studies reported both in vitro and in vivo that R-LPS could benefit from the presence of CD14 [24,46]. Accordingly, several other studies have described R-LPS as a more potent agonist of the innate immune system than S-LPS [42,4649]. Overall, such findings are consistent with our results showing that the shorter LPS naturally signals more via TRIF than the full-length LPS, and that sCD14 contributes to this enhanced signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This would be consistent with previous studies showing that smooth LPS (S-LPS) depends on CD14 to activate cells [ 40 , 43 ]. On the other hand, it is established that rough LPS (R-LPS) depends on CD14 mainly for TLR4 endocytosis [ 21 , 22 ], although some studies reported both in vitro and in vivo that R-LPS could benefit from the presence of CD14 [ 21 , 44 ]. Accordingly, several other studies have described R-LPS as a more potent agonist of the innate immune system than S-LPS [ 40 , 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, under these conditions, MECs markedly overexpressed (mRNA) CCL20, a chemokine that attracts cells expressing the receptor CCR6, which include most of type 3 immunity cells [25]. This chemokine was found at the protein level in milk from bovine MGs exposed to E. coli LPS [26].…”
Section: What We Know About Type 3 Immunity In the Mammary Glandmentioning
confidence: 94%